Fostering Tertiary Student Professional Mobility Skills via Convergence of the Professional Training and Foreign Language Learning - Valentyna I. Bobrytska* (RU Publications, 2021)
The purpose of the study was to identify how the instructional model that converges professional training and foreign language learning can influence the students’ professional mobility and students’ readiness to build their careers. The study used the methods of a quantitative kind for the evaluation study and descriptive research. The variables for the study were as follows: levels of student professional mobility skills proficiency that included students’ competence in their professional field, foreign language proficiency, students’ networking skills, personality qualities, and sampled students’ satisfaction with the reshaped course. The field phase of the study found that the Erasmus and Work-and-Travel programmes contributed to the former students’ adaptability and flexibility, the experience of work abroad, and practical specialism-related experience gained during study. The students developed their abilities to project a positive social image, ability to build and maintain relationships, foreign language proficiency, proficiency in presenting and negotiating, and theoretical knowledge. The English Language-delivered Professional Mobility course brought shifts in the levels of students’ professional mobility skills. The experimental group students reported that they improved their competence in their professional field, foreign language proficiency, networking skills, and personality qualities. The experimental group students’ judgements concerning the quality of the course were complimentary.